Modelling of high speed micro end milling of poly methyl methaacrylate on system parameters - Nur Atiqah binti Abdul Rahman Azmil (Kulliyyah of Engineering, International Islamic University Malaysia, 2014)
Micro end milling is one of the most important micromachining process and widely used for producing miniaturized components with high accuracy and surface finish. Due to the machining parameters, vibration also accords with the deterioration of the surface quality and material removal rate. Thus, this research investigates the influence of three micro end milling process parameters; spindle speed, feed rate, and depth of cut on vibration, surface roughness, and material removal rate. The response variables were tool vibration (Vt), workpiece vibration (Vm), surface roughness (Ra), and material removal rate (MRR). The machining was performed using multi-process micro machine tools (DT-110 Mikrotools Inc., Singapore) with poly methyl methacrylate (PMMA) as the workpiece and tungsten carbide as its tool. To develop the mathematical model for the responses in high speed micro end milling machining, Taguchi design has been used to design the experiment by using the orthogonal array of three levels L18 (21×37). From the results, the high speed phenomena in micro end milling have been investigated with significant results with all objectives successfully fulfilled. The analysis revealed minimum Vt, Vm, Ra, and maximum MRR with desirability of 86.5%. The optimized values of Vt, Vm, Ra, and MRR were 71.48 Hz, 59.16 Hz, 128.24 nm, and 0.0463 mg/min, respectively obtained at spindle speed of 30000 rpm, feed rate of 2.65 mm/min, and depth of cut of 40 μm.